Selection of Proteins and Construction of Derivative Adapted for Single Molecule Investigation - Yovin
Single molecule Förster-resonance energy-transfer (smFRET), is an essential technique to study dynamics of proteins via probing conformational changes in real time. In a recent study, it is intriguing to investigate the function of the proteins (i.e. ligand binding mechanism) by following their dynamics at single molecule level. However, detection of conformational changes requires appropriate protein derivative adapted for single-molecule investigation. In the protein derivative, a Cysteine pair is placed at strategic positions that fulfill at least three criteria, namely respond protein dynamics marked by significant distance changes; highly exposed for efficient fluorophore attachment; involve non-conserved residues for not compromising protein function; and with additional criteria is some residues on the sequence could be changed with the same chemical characteristic as cysteine residue. In previous studies, our group has analyzed proteins having a common fold termed as “cherry-fold”. The “cherry-fold” composes of two rigid domains connected by two antiparallel ?-strands. These proteins are derived from a common structural ancestor and they are different classes (A-G) having distinct tails attached to the “cherry-fold”. Class A protein have a short C-tail and lock and key ligand binding mechanism. Class B, C and G have a longer C-tail than class A and show induced fit ligand binding mechanism. It is also found that the C-tails dictate the binding mechanism by stabilizing specifically a conformational state. Proteins from classes A, D, E, and F are remain to be found out. In this study, proteins from classes A, D, E, and F that want to be found out and for single molecule investigations were selected and adapted. The following proteins: OxyR from Pseudomonas aeruginosa for class A, PhnD from Escherichia coli for class D, CmpA from Synechocystis sp. for class E, and nFbp from Neisseria gonorrhoeae for class F were chosen. Identification of the genome sources and suitable expression system were first performed. The gene corresponding to each protein from all classes was then isolated by PCR (Polymerase Chain Reaction) with the respective genomes as template and appropriate primer pairs. The amplified genes were subsequently inserted into the E. coli expression vector pET-16b. The gene was verified by DNA sequencers. In vitro translation analysis showed that all proteins were have the identical sequence with protein sequence retrieved from PDB (Protein Data Bank). Cysteine analysis has been done by analyzing all protein residues with ConsurfDB online server to identify conservation score and with SWISS PDB Viewer to analyse surface exposure. For FRET experiments, it is also critical to consider the distance changes among two residual probes between open and close state of the protein. Distance analysis has been done manually using PyMOL to calculate distance chages between open and close state. Cysteines were then placed in the proteins at strategic positions according to the criteria already mentioned by site-directed mutagenesis using mutation primer and PCR. All proteins were expressed by induction with 300 ?M IPTG and purified using metal-affinity chromatography (Ni-sepharose resin) with elution buffer containing 500 mM imidazole. Based on SDS-PAGE electrophoregram, pure proteins have been successfully obtained and could be used for further single-molecule investigations.